Structural, vibrational and electronic characterization of 1-benzyl-3-furoyl-1-phenylthiourea: an experimental and theoretical study1. (24th September 2015) - Defonsi Lestard, María Eliana; Gil, Diego M.; Estévez-Hernández, Osvaldo; Erben, Mauricio F.; Duque, Julio
<x xml:space="preserve">Abstract</x> The compound 1-benzyl-3-furoyl-1-phenylthiourea was synthesized and characterized through IR and Raman spectroscopy and its molecular structure was determined.